(untitled) (Educational Perspectives Magazine (REPED), 2022)
This paper is about the important and need to introduce democratic practices in the classroom, as a way to build knowledge at school. Consenquently, teaching formation becomes a fundamental issue lo get competences to start democratic practices in future teachers. Furthermore, it is evident how important it is to edúcate reflective and critical knowledge builder children at school. Similarly, teaching innovation is seen as a tool to make constructive practices of a comprehensive school.